1997
DOI: 10.2307/3284379
|View full text |Cite
|
Sign up to set email alerts
|

A New Hepatozoon Species from Dogs: Description of the Causative Agent of Canine Hepatozoonosis in North America

Abstract: A new species of Adeleina, Hepatozoon americanum, is described from the skeletal muscle, cardiac muscle, visceral organs, and blood of dogs (Canis familiaris) in the Southern United States. The organism was previously identified as Hepatozoon canis (James, 1905) Wenyon, 1926; however, differences in clinical signs, histopathological and serological findings, gamont size, and ultrastructure define the new species of Hepatozoon. Attempts to transmit the protozoan from infected dogs to nymphal Rhipicephalus sangu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
60
2
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(78 citation statements)
references
References 15 publications
7
60
2
7
Order By: Relevance
“…Our results and those from other studies (Vincent-Johnson et al, 1997;Perkins and Keller, 2001;Simpson et al, 2006b;Criado-Fornelio et al, 2006) demonstrate the value of molecular techniques to reveal the evolutionary relationship between morphologically similar Hepatozoon species.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Our results and those from other studies (Vincent-Johnson et al, 1997;Perkins and Keller, 2001;Simpson et al, 2006b;Criado-Fornelio et al, 2006) demonstrate the value of molecular techniques to reveal the evolutionary relationship between morphologically similar Hepatozoon species.…”
Section: Discussionsupporting
confidence: 84%
“…Clinical signs consistent with those reported for Hepatozoon infections in domestic dogs (Hervas et al, 1995;Baneth et al, 1997;Vincent-Johnson et al, 1997) and experimentally infected coyote (Canis latrans) pups (Kocan et al, 2000) were observed in two young spotted hyena cubs. The death of both these young hyena cubs may indicate that Hepatozoon infection is mostly associated with mortality in young spotted hyenas, and if so, the effect of Hepatozoon infection on wild carnivore populations may be underestimated.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations